Incision wound healing activity of free-range chicken (Gallus domesticus) egg white gel in mice - Wahyu Widyaningsih; Sapto Yuliani; Ayu Wulandari; Rifka Salsabila (Universitas Ahmad Dahlan, 2021)
Egg whites reportedly exhibit wound healing activities by forming new cell tissues and accelerating damaged cell tissue recovery. This study aimed to determine whether and how egg whites prepared in gel dosage forms healed incision wounds in mice (Mus musculus). The method began with formulating gels by mixing egg whites with Carbopol 940, methylparaben, propylparaben, propylene glycol, triethanolamine, and distilled water. Sixteen mice were divided evenly into four groups, and each was subjected to a 1 cm long midline dorsal incision. Group I was given 10% povidone-iodine ointment, group II was gel base, group III was 10% egg white gel, and group IV was 20% egg white gel. Based on the test parameters measured during macroscopic observation, namely wound length and healing time, the gel preparations were found to fulfill the physical properties requirements, and incision wounds treated with 10% and 20% egg white gels healed in 9 and 12.5 days, respectively. The statistical test revealed a significant difference in wound size on Day 10 and in healing time between wound treatments with 10% gel and base gel (p < 0.05). Therefore, it can be concluded that the 10% egg white gel is effective in healing cuts in mice as it speeds wound healing and decreases wound size.